Fetish in Amateur Photography Practices - Hartono Karnadi (Graduate School of Institut Seni Indonesia Yogyakarta, 2022)
People, including amateur photographers, have been experiencing development on digital technology. Amateur phothographers are those who practicing photography as a hobby and join a photography club. Although at first people doubted the quality and performance of the digital tecnology, until now it has been growing to become a fetish. In the practice domain, it is cherished as a god-powered machine able to do incredible tasks. This research aimed at studying the psychological and sociological conditions of amateur photographers at the shift of technology from analog to digital photography and close to the the post-digital era. Technology transformation has brought about significant impacts on photographers’ perspective about creating, displaying, and publishing photographs. The qualitative data were collected from literature study and interviews with senior photographers famous for their achievements among the amateurs, especially those who joined the Salonfoto Indonesia. The result of this study shows that fetishism on digital technology in amateur photographers’ practices does not automatically become the only method employed in exploring their creativity sources. Based on the aesthetical experiences of the amateurs, it can be concluded that digital technology functions only as a computing system to perfect the creative works. Technigue is important but not the most important one. Fetis dalam Praktik Fotografi Amatir Abstrak Perkembangan digital sangat dirasakan oleh semua orang termasuk fotografer amatir. Mereka termotivasi untuk pengembangan diri, bersosialisasi dan berpartisipasi dalam kontes fotografi. Walaupun pada awalnya diragukan dalam performa kualitasnya. Dalam praktiknya, teknologi digital seperti mesin yang menjadi dewa, ia menjadi fetis, seolah-olah memiliki kekuatan yang luar biasa untuk menghasilkan foto yang bagus. Penelitian ini mengkaji kondisi-kondisi psikologis dan sosiologis amatir sebagai akibat dari peralihan teknologi analog ke digital dan menjelang pasca digital. Dampak transformasi teknologi sangat memengaruhi perspektif dalam mencipta, menyajikan, dan mempublikasikan foto mereka. Metode pengumpulan data menggunakan kualitatif yang bersumber pada studi kepustakaan dan mewawancarai beberapa fotografer senior yang sudah sangat dikenal prestasinya di kalangan amatir, khususnya Salonfoto Indonesia. Hasil awal dari penelitian ini menunjukkan tranformasi teknologi digital mengubah paradigma amatir senior, yang semula menganggap digitalisasi merupakan mesin rumit dan membingungkan, sehingga mereka berusaha mempertahankan nilai-nilai 'tradisional' fotografi analog yang mengutamakan proses manual. Kesimpulan yang dapat dirangkum bahwa fetisisme teknologi digital dalam praktik fotografer amatir, tidak serta-merta menjadi satu-satunya metode yang dapat mendukung eksplorasi sumber daya ciptanya. Berdasarkan pengalaman estetika amatir, teknologi digital hanya sebagai suatu sistem komputasi untuk menyempurnakan olah kreatif. Teknis penting, tapi bukan yang terpenting!